ANALISIS KINERJA AGRIBISNIS VANILI DI KABUPATEN SUMEDANG, JAWA BARAT - Setiawan, Darma; Setiawan, Iwan; Wulandari, Eliana (Universitas Galuh, 2023)
Vanilla is a plantation crop commodity that has high economic value. As one of the world's vanilla-producing countries, Indonesia's vanilla production must maintain supply for the domestic consumption market and the world export market. The irony is while the demand for foreign markets is increasing, domestic demand for vanilla has just been covered. The continuity of vanilla supply in meeting the needs of domestic and foreign markets is primarily determined by the performance of the vanilla agribusiness itself. Some of the problems in the agribusiness system include the uneven use of superior seeds, weak cultivation technology adoption, and weak institutional innovation. This study aims to determine the performance of vanilla agribusiness in Sumedang Regency. The method used is descriptive with a quantitative approach. Data was collected using a survey method through interviews and questionnaires conducted from November to December 2022 in Cimalaka District and Surian District, Sumedang Regency, with a sample determined using proportional stratified random sampling of 67 farmers. The results showed that the performance of the input supply, cultivation, marketing and support subsystems was in a suitable category, with the performance of the marketing subsystem having the highest performance and the cultivation subsystem having the lowest performance. Meanwhile, the harvest and postharvest subsystems performed exceptionally well. The performance of the vanilla agribusiness system can be increased by improving each subsystem. To improve the performance of vanilla agribusiness, it is necessary to strengthen the performance of each subsystem, especially in the cultivation and harvest and postharvest subsystems.